TREK-1 (K2P2.1) K+ channels are suppressed in patients with atrial fibrillation and heart failure and provide therapeutic targets for rhythm control - Lugenbiel, Patrick; Wenz, Fabian; Syren, Pascal; Geschwill, Pascal; Govorov, Katharina; Seyler, Claudia; Schweizer, Patrick Alexander; Franke, Jennifer; Weis, Tanja; Bruehl, Claus; Schmack, Bastian; Ruhparwar, Arjang; et al. (Basic research in cardiology, 2017)
Atrial fibrillation (AF) is the most common cardiac arrhythmia. Concomitant heart failure (HF) poses a particular therapeutic challenge and is associated with prolonged atrial electrical refractoriness compared with non-failing hearts. We hypothesized that downregulation of atrial repolarizing TREK-1 (K2P2.1) K+ channels contributes to electrical remodeling during AF with HF, and that TREK-1 gene transfer would provide rhythm control via normalization of atrial effective refractory periods in this AF subset. In patients with chronic AF and HF, atrial TREK-1 mRNA levels were reduced by 82% (left atrium) and 81% (right atrium) compared with sinus rhythm (SR) subjects. Human findings were recapitulated in a porcine model of atrial tachypacing-induced AF and reduced left ventricular function. TREK-1 mRNA (−66%) and protein (−61%) was suppressed in AF animals at 14-day follow-up compared with SR controls. Downregulation of repolarizing TREK-1 channels was associated with prolongation of atrial effective refractory periods versus baseline conditions, consistent with prior observations in humans with HF. In a preclinical therapeutic approach, pigs were randomized to either atrial Ad-TREK-1 gene therapy or sham treatment. Gene transfer effectively increased TREK-1 protein levels and attenuated atrial effective refractory period prolongation in the porcine AF model. Ad-TREK-1 increased the SR prevalence to 62% during follow-up in AF animals, compared to 35% in the untreated AF group. In conclusion, TREK-1 downregulation and rhythm control by Ad-TREK-1 transfer suggest mechanistic and potential therapeutic significance of TREK-1 channels in a subgroup of AF patients with HF and prolonged atrial effective refractory periods. Functional correction of ionic remodeling through TREK-1 gene therapy represents a novel paradigm to optimize and specify AF management.
First online: 22 December 2016
Im Titel ist 2P tiefgestellt und + hochgestellt
Gesehen am 18.06.2018